2011
DOI: 10.3324/haematol.2010.030320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the use of autologous stem cell transplantation at first relapse both in naive and previously rituximab exposed follicular lymphoma patients treated in the GELA/GOELAMS FL2000 study

Abstract: BackgroundWe analyzed detailed characteristics and salvage treatment in 175 follicular lymphoma patients from the FL2000 study who were in progression after first-line therapy with or without addition of rituximab to chemotherapy and interferon. Design and MethodsThe impact of using autologous stem cell transplantation and/or rituximab administration at first progression was investigated, taking into account initial therapy. With a median follow up of 31 months, 3-year event free and overall survival rates aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 20 publications
(22 reference statements)
6
55
0
Order By: Relevance
“…Moreover, it remains to be shown in FL if relapse after rituximab-containing first-line treatment is associated with a poorer prognosis than relapse after rituximab-free treatment 31 as seems to be the case with aggressive B-cell lymphoma. 32 The role of HDT-ASCR in patients with relapsed FL in the rituximab era is supported by the studies published by Sebban et al 33 and Le Gouill et al 34 Moreover, a recent EBMT study has demonstrated that rituximab does EBMT FL transplant consensus haematologica | 2013; 98 (7) 1017 Table 5. Statements for which no consensus was achieved.…”
Section: *Partial Consensus Onlysupporting
confidence: 54%
“…Moreover, it remains to be shown in FL if relapse after rituximab-containing first-line treatment is associated with a poorer prognosis than relapse after rituximab-free treatment 31 as seems to be the case with aggressive B-cell lymphoma. 32 The role of HDT-ASCR in patients with relapsed FL in the rituximab era is supported by the studies published by Sebban et al 33 and Le Gouill et al 34 Moreover, a recent EBMT study has demonstrated that rituximab does EBMT FL transplant consensus haematologica | 2013; 98 (7) 1017 Table 5. Statements for which no consensus was achieved.…”
Section: *Partial Consensus Onlysupporting
confidence: 54%
“…three-quarters (73%) as recently reported in FL2000 patients with treatment failure after first-line therapy) and also probably accounted for the limited difference in OS. 24 Concerning prognosis and within the limits of patient numbers, all potential prognostic factors were overridden by the strong predictive power of the FLIPI in the present cohort.…”
Section: Discussionmentioning
confidence: 96%
“…Other series have confirmed the lack of a detrimental effect of prior rituximab before HDT for FL and have actually suggested that patients who receive both rituximab and HDT at relapse have a significantly better outcome than the remainder. 25,26 This is reassuring as the population of patients candidate for HDT-ASCR who are rituximab-naïve is shrinking and most patients proceeding to HDT/ASCT have already received rituximab.…”
Section: -Year Ttpmentioning
confidence: 99%